2012
DOI: 10.1186/1477-7525-10-14
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of quality of life instruments in long-term breast cancer survivors

Abstract: BackgroundBreast cancer is the most common cancer in women, representing 16% of all female cancers. According to the American Cancer Society, long-term cancer survival is defined as more than five years of survivorship since diagnosis, with approximately 2.5 million breast cancer survivors (BCS) in 2006. The long-term effects from breast cancer and its treatment have been shown to have positive and negative effects on both recovery and survivors' quality of life (QoL). The purpose of the study was to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
96
0
10

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(109 citation statements)
references
References 45 publications
3
96
0
10
Order By: Relevance
“…The most significant aspect of QoL mentioned as psychological well-being in many studies (Vanderwerker et al, 2005;Wagner et al, 2006;Badger et al, 2007) although QoL has multidimensional aspects (Ogce et al, 2008;Yanez et al, 2011;Chopra and Kamal, 2012). Studies examining demographic variables and psychosocial characteristics of caregivers related to QoL found that being a woman, younger age, single, lower socioeconomic status, unemployment, low education (Mellon et al, 2006;Gorji et al, 2012) and also lack of personal and social support (Ogce et al, 2008) affect the QoL negatively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most significant aspect of QoL mentioned as psychological well-being in many studies (Vanderwerker et al, 2005;Wagner et al, 2006;Badger et al, 2007) although QoL has multidimensional aspects (Ogce et al, 2008;Yanez et al, 2011;Chopra and Kamal, 2012). Studies examining demographic variables and psychosocial characteristics of caregivers related to QoL found that being a woman, younger age, single, lower socioeconomic status, unemployment, low education (Mellon et al, 2006;Gorji et al, 2012) and also lack of personal and social support (Ogce et al, 2008) affect the QoL negatively.…”
Section: Discussionmentioning
confidence: 99%
“…These issues are natural results of the disease. And studies indicate that women's Quality of life (QoL) is affected with multidimensional areas, including emotional, physical, sexual, and social domains (Yanez et al, 2011;Chopra and Kamal, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is the most common cancer among women (46). It is a heterogeneous (47) disease with multiple clinical, pathological and molecular forms (48).…”
Section: Discussionmentioning
confidence: 99%
“…It is a heterogeneous (47) disease with multiple clinical, pathological and molecular forms (48). The most important risk factors for the disease include gender, age and ethnicity (46). Its incidence and mortality rates generally increase with age, so that women over 45 present greater risk (46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation